The dynamism of the social and personal in Philosophy of Historical Reality.: A rereading from Ellacuría's anthropology - Martínez Vásquez, Luis Arturo (2025)
Ellacuría's anthropology continues Zubiri's work, in which the dynamics of reality constitute a metaphysical unity. In Philosophy of Historical Reality, the dynamism of biological life allows for the implication of the social and the personal, with a biological and chronological priority given to the social.